2011
DOI: 10.1371/journal.pone.0014744
|View full text |Cite
|
Sign up to set email alerts
|

Human Auditory Cortical Activation during Self-Vocalization

Abstract: During speaking, auditory feedback is used to adjust vocalizations. The brain systems mediating this integrative ability have been investigated using a wide range of experimental strategies. In this report we examined how vocalization alters speech-sound processing within auditory cortex by directly recording evoked responses to vocalizations and playback stimuli using intracranial electrodes implanted in neurosurgery patients. Several new findings resulted from these high-resolution invasive recordings in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 54 publications
12
112
2
Order By: Relevance
“…We previously predicted such a role of vocalization-induced suppression based upon neural activities during frequency-shifted changes in vocal feedback (Eliades and Wang, 2008a). Recent evidence from human studies confirms this increase in auditory cortex sensitivity during speech (Behroozmand et al, 2009;Greenlee et al, 2011). It has also been suggested that suppression occurs when there is a match between expected and perceived feedback, and that the increased activity during masking reflects a mismatch due to absence or reduced feedback (Houde et al, 2002).…”
Section: Masking and The Origins Of Vocalization-induced Suppressionmentioning
confidence: 90%
See 1 more Smart Citation
“…We previously predicted such a role of vocalization-induced suppression based upon neural activities during frequency-shifted changes in vocal feedback (Eliades and Wang, 2008a). Recent evidence from human studies confirms this increase in auditory cortex sensitivity during speech (Behroozmand et al, 2009;Greenlee et al, 2011). It has also been suggested that suppression occurs when there is a match between expected and perceived feedback, and that the increased activity during masking reflects a mismatch due to absence or reduced feedback (Houde et al, 2002).…”
Section: Masking and The Origins Of Vocalization-induced Suppressionmentioning
confidence: 90%
“…Another recent study, using altered feedback, demonstrated feedback sensitivity in the auditory nuclei of juvenile zebra finches including field-L, the analog of the mammalian auditory cortex (Keller and Hahnloser, 2009). Interestingly, although these auditory nuclei are feedback sensitive like the mammalian auditory cortex, their neural activity during normal song production closely parallels that during song playback and does not exhibit the same degree of prominent vocalization-induced suppression common to both humans (Crone et al, 2001;Houde et al, 2002;Flinker et al, 2010;Greenlee et al, 2011) and nonhuman primates (Eliades and Wang, 2003).…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
“…Many human fMRI and electrocorticography studies reporting attenuation have compared speech production with passive listening to speech sounds 17,18 . While the appeal of using speech as a natural stimulus is clear, it nonetheless introduces difficulties in equating the physical attributes of the sound between the passive and active conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Using transcranial magnetic stimulation (TMS), it has been shown that even during motor preparation (that is, before the actual motor act) sensitivity to sensory stimuli is already reduced 16 . Invasive studies in patients, using electrocorticography show mostly suppressed responses in superior temporal gyrus (STG) to self-vocalization versus passive listening to similar speech sounds 17,18 .…”
mentioning
confidence: 99%
“…We refer to this area as the posterolateral superior temporal auditory area (PLST). This area, which may comprise more than one functional field, responds robustly to a wide range of stimuli, including pure tones, trains of acoustic clicks, modulated noise bursts, and speech utterances (Reale et al 2007;Brugge et al 2008b;Nourski et al 2010;Greenlee et al 2011;Nourski et al 2013a, b).…”
Section: Introductionmentioning
confidence: 99%